Research on security scenarios and security models for 6G networking - Chenglei ZHANG; Yulong FU; Hui LI; Jin CAO (网络与信息安全学报)
The concept of 6G has been proposed and has attracted the wide attention of academe.Generally speaking, the 6G network will optimize the performance of 5G, and expand the network scenarios which are difficult to achieve within 5G.However, the introduction of new scenarios and technologies will also bring new security threats to cyber security.The research progress on the key technologies and implementation methods of the 6G were conducted.To summarize a vision of core technologies of 6G, the research work of major 5G/6G research institutions, companies and enterprises were focused on .On this basis, the possible security problems and security challenges in 6G network were put forward.Finally, according to the existing network techniques, the possible solutions and proposed a general security model for 6G networks were discussed.